1981
DOI: 10.2224/sbp.1981.9.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Retarding the Escalation of Aggression

Abstract: Three experiments examined the inhibition of escalation of aggression. Subjects either punished incorrect or rewarded correct responses made by a confederate on a learning task. In Experiment 1, some subjects were interrupted midway through the learning trials, and some of the interrupted subjects coded their responses up to that point. The interruption and coding had no effect on escalation of reinforcement intensity over trials. In Experiment 2, half the subjects were individuated and half were de-individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…It may be argued that the strong balls we adopted here are insufficiently aversive to be comparable with real-life bullying. However, it is reported that aggression often begins at a low level, such as teasing or cursing, and escalates to more injurious behavior (Taylor et al , 1979; Goldstein et al , 1981). Therefore, we think that this task is appropriate for investigating the early stage of bullying.…”
Section: Discussionmentioning
confidence: 99%
“…It may be argued that the strong balls we adopted here are insufficiently aversive to be comparable with real-life bullying. However, it is reported that aggression often begins at a low level, such as teasing or cursing, and escalates to more injurious behavior (Taylor et al , 1979; Goldstein et al , 1981). Therefore, we think that this task is appropriate for investigating the early stage of bullying.…”
Section: Discussionmentioning
confidence: 99%
“…While escalation effects may begin over petty issues, the final level of hostilities is out of all proportion to the magnitude of the original provocation (J.H. Goldstein, Davis, & Herman, 1975;J.H. Goldstein, Davis, Kernis, & Cohn, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…A number of plausible suggestions for halting the upward spiral of interpersonal exchanges have been tested (J.H. Goldstein, Davis, Kernis, & Cohn, 1981). The results are not encouraging.…”
Section: Escalation Of Aggressionmentioning
confidence: 99%
“…Despite these early findings, several other findings found no evidence of the deindividuation state 35 , 36 and a meta-analysis conducted by Postmes and Spears 37 of sixty empirical studies showed little support for the existence of the deindividuation phenomenon. Furthermore, early studies focused more on anti-normative behaviors in the form of increased antisocial behaviors and showed little evidence that it would lead to decreased prosocial behaviors.…”
Section: The Effect Of Reduced (Perceived) Identifiabilitymentioning
confidence: 90%